B2M gene expression shapes the immune landscape of lung adenocarcinoma and determines the response to immunotherapy. Issue 3 (21st June 2021) - Zhao, Yu; Cao, Yuejiao; Chen, Yiqi; Wu, Lei; Hang, Hua; Jiang, Chenxia; Zhou, Xiaorong
Abstract: Loss of the B2M gene is associated with tumour immune escape and resistance to immunotherapy. However, genetic alterations of the B2M gene are rare. We performed an integrative analysis of the mutational and transcriptional profiles of large cohorts of non‐small‐cell lung cancer (NSCLC) patients and found that epigenetic downregulation of B2M is common. B2M‐low tumours exhibit a suppressive immune microenvironment characterized by reduced infiltration of immune cells of various lineages; in B2M‐high tumours, more T and natural killer cells are present, but their activities are constrained by immune checkpoint molecules, indicating the diverse mechanisms of immune evasion. High levels of B2M mRNA, but not PD‐L1, are correlated with an enhanced response to PD‐1‐based immunotherapy, suggesting its value for immunotherapy response prediction in solid tumours. Notably, a high tumour mutation burden (TMB) is associated with low B2M expression, which may explain the poor predictive value of the TMB in some situations. In syngeneic mouse models, genetic ablation of B2M in tumour cells causes resistance to PD‐1‐based immunotherapy, and B2M knockdown also diminishes the therapeutic efficacy. Moreover, forced expression of B2M in tumour models improves the response to immunotherapy, suggesting that B2M levels have significant impacts on treatment outcomes. Finally, we provide insight into the roles of transcription factors and KRAS mutations in B2M expression and the anticancer immune response. In conclusion, genetic and epigenetic regulation of B2M fundamentally shapes the NSCLC immune microenvironment and may determine the response to checkpoint blockade‐based immunotherapy. Abstract : Anti‐PD‐1 immunotherapy has significantly improved the survival of patients with lung cancer, but drug resistance greatly limited its long‐term benefits. We found that a defective B2M gene expression is the underlying mechanism of the resistance, and we proposed some potential strategies to improve the efficacy of anit‐PD‐1 immunotherapy and overcome the resistance.